Comparison between the lecture and jigsaw methods for fourth year nursing students - Sidarong, Sun
Use of effective teaching methods is critical in improving learning outcomes. The lecture is an effective means of imparting information. However, students aside from gaining knowledge need to achieve other outcomes including ability to actively search knowledge and develop communication skills. The jigsaw method is a strategy that requires students to independently seek knowledge and engage in peer-to-peer teaching. The purpose of this research is to compare the effectiveness of two teaching-learning strategies, namely traditional lecture and Jigsaw as small group learning among 80 fourth-year students in Bachelor?s Degree in Nursing. This study uses a cross-over-experimental study in an offered course in Technical School for Medical Care in Cambodia in the academic year 2016-2017. The population consists of 80 fourth-year nursing students, those who gave consent to be part of the study will be randomly divided into two groups, A and B. All completed a brief multiple-choice pre-test. Later, assigned students in group A start with a lecture and group B with Jigsaw for the first session. The second session, students group A participants in Jigsaw, students group B learns with teacher lecture. After finishing both sessions, all students took a classroom post-test identical to the pre-test. Data to be collected will mainly be pre-test and post-test, questionnaire, classroom observation and focus group discussion. The study revealed significant difference in cognitive outcomes between lecture and jigsaw methods. The increase of learning outcome was 4.25% in lecture and 10.4% in the jigsaw. The result of pretest and posttest score had shown that students who were taught jigsaw method improved their knowledge than students who were taught lecture method. However, both teaching strategies were reported to reveal posttest score less than 50%, which meant these teaching strategies failed to reach the level of knowledge expected of students. Moreover, the result of the rating scale and focus group discussion about students? satisfaction and their experiences revealed more positive feedbacks on jigsaw than lecture method. Conducting innovative teaching and learning strategies in one session setting was not sufficient in achieving learning outcomes. In order to maximize learning for students, they needed to have knowledge and skills in using the English language, accessing the Internet, and searching for appropriate information